Degradação de bifenilos policlorados (PCBs) por microrganismo de interesse tecnológico na indústria cárnea - Leães, Fernanda Leal (2005)
Due to the risk for human health associated to the presence of polychlorinated biphenyl (PCB) residues in foods, there is an interest in knowing the different factors that could reduce such contamination. Previous research has demonstrated that food processing modifies both qualitative and quantitatively, the organochlorine contamination, specially PCBs, of the raw material. Further, microorganisms of technological interest in food industry could play an important role in the degradation process. The growth of the meat starter Staphylococcus xylosus in liquid media containing PCBs (10, 28, 52, 138, 153 and 180), and its ability to degrade PCBs during 168 h of incubation in liquid media and meat mixture was investigated. PCBs did not affect the growth of the starter microorganism in nutritive (brain heart infusion, BHI) or mineral salt medium (MSM) when compared to control (no PCB). The microorganism was able to degrade some of the PCB congeners tested. PCBs 138 and 153 were degraded both in BHI (78% and 68%, respectively; p<0.05) and in MSM (71% and 66%, respectively; p<0.05), with maximal being observed within 24 hours. Highly significant negative exponential relationships were observed between incubation time and PCB 28 and 180 in BHI, as well as to PCBs 52 and 180 in MSM. In the meat mixture highly significant negative exponential relationships were observed between incubation time and the concentration of PCB 10. These results indicate that fermentation by Staphylococcus xylosus in meat products can reduce some PCB residues and the meat starter can be used to obtain foods with lower toxicological risk.